Does One Dose Really Fit All? On the Monitoring of Direct Oral Anticoagulants: A Review of the Literature - Moner-Banet, Thomas; Alberio, Lorenzo; Bart, Pierre-Alexandre (Hämostaseologie, 2020)
Background There is an increasing amount of literature on direct oral anticoagulant (DOAC) laboratory monitoring. The aims of the present review were to evaluate published data on monitoring DOACs, to provide clinical guidance on how to interpret results, and to summarize why, when, and how to monitor DOACs.Methods The publications screened for this review were obtained through a PubMed search for articles published in English or French before April 2019 that had the following as their main themes: DOAC monitoring, DOAC exposure–effect relationship, DOAC drug interactions, and pharmacokinetics and pharmacodynamics of DOACs.Results DOACs show important inter- and intrapersonal concentration variability and a significant exposure–effect relationship. Concentrations out of the expected range have been shown to lead to an increased adverse event rate and a lower efficacy. No definitive therapeutic range exists for DOACs except for dabigatran for which trough levels of 40 to 200 ng/mL seem to be the consensus. Indications to monitor include suspected drug accumulation in special patient populations, suspected drug failure, and acute situations such as hemorrhagic or thrombotic events.Conclusion There is a likely benefit to monitor DOACs in order to improve their safety and efficacy but randomized controlled trials are required to determine the therapeutic range of these drugs and evaluate whether DOAC monitoring can improve outcomes in a clinical setting.
Keywords: direct oral anticoagulant; monitoring; dose tailoring; plasma level